2001
DOI: 10.1037/0022-0167.48.2.178
|View full text |Cite
|
Sign up to set email alerts
|

Correspondence of interests and abilities with occupational choice.

Abstract: The correspondence of interests and self-estimates of ability with occupational choice was examined in a nationally representative sample of high school seniors (N = 4,679). Correspondence was examined with D. J. Prediger's (1982) things-people and data-ideas dimensions on interests, ability self-estimates, and occupational choice by means of canonical correlation analyses. Interests and abilities were found to have a high level of correspondence with occupational choice and to overlap in their correspondence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
73
1
4

Year Published

2002
2002
2020
2020

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 92 publications
(81 citation statements)
references
References 57 publications
3
73
1
4
Order By: Relevance
“…This is in line with more general research that has shown that individuals' perceptions of their capabilities (i.e., self-efficacy) are related to their preferences for performing specific tasks (Bandura, 1977;Betz & Hackett, 1981). People tend to avoid engaging in tasks for which their self-efficacy is low and generally pursue tasks for which their self-efficacy is high (e.g., Tracey, 1997;Tracey & Hopkins, 2001).…”
Section: Gender Differences In Individual Task Choicesupporting
confidence: 87%
“…This is in line with more general research that has shown that individuals' perceptions of their capabilities (i.e., self-efficacy) are related to their preferences for performing specific tasks (Bandura, 1977;Betz & Hackett, 1981). People tend to avoid engaging in tasks for which their self-efficacy is low and generally pursue tasks for which their self-efficacy is high (e.g., Tracey, 1997;Tracey & Hopkins, 2001).…”
Section: Gender Differences In Individual Task Choicesupporting
confidence: 87%
“…The extent to which interests and self-efficacy in combination can provide incremental utility in the career counseling process is of considerable practical as well as theoretical importance. Major studies demonstrate the incremental predictive validity of these two sets of variables (Donnay & Borgen, 1999;Isaacs, Borgen, Donnay, & Hansen, 1997;, Rottinghaus, Lindley, Green, & Borgen, 2002Tracey & Hopkins, 2001), yet there have been few studies of counseling interventions based on use of the cross-classifications suggested herein. Furthermore, tests of the SCCT model require the availability of parallel measures of self-efficacy and interests (and, ideally, outcome expectations), so we hope that the availability of these many new sets of parallel measures will stimulate broader examination of SCCT and related models.…”
Section: Future Directionsmentioning
confidence: 99%
“…Although not all studies that followed Donnay and Borgen used the same approach to statistical analyses, the findings that interests and self-efficacy make incremental contributions to the prediction of major and occupational choice and group membership have been frequently replicated (e.g., see Betz, Borgen, & Harmon, 2006;Tracey & Hopkins, 2001), and the joint use of interest and confidence scores in career assessment and counseling has gained considerable acceptance (see the review by Betz & Rottinghaus, 2006).…”
Section: Incremental Predictive Validitymentioning
confidence: 99%